Foods for Special Medical Purposes in Home Enteral Nutrition-Clinical Practice Experience. Multicenter Study - Folwarski, Marcin; Kłęk, Stanisław; Zoubek-Wójcik, Agata; Szafrański, Waldemar; Bartoszewska, Lidia; Figuła, Krzysztof; Jakubczyk, Marlena; Jurczuk, Anna; Kamocki, Zbigniew; Kowalczyk, Tomasz; Kwella, Bogna; Matras, Przemysław; et al. (Frontiers in Nutrition, 2022)
Background Enteral nutrition (EN) with foods for special medical purposes (FSMP) is recommended for most patients on home enteral nutrition (HEN). Although there are disease-specific guidelines for energy, protein, and micronutrient provision, only a few studies are showing real-life experience in the long-term use of FSMP. Methods In a multicenter study, the influence of the FSMP composition and administration technique (bolus vs. continuous) on protein and energy provision in HEN was analyzed. Provision of vitamins and minerals was compared to recommended daily allowance (RDA) and upper tolerable limit (UL). Results Approximately, 772 patients on HEN, mostly (88.6%) with oncological and neurological diseases, were enrolled. The patients on standard FSMP received less protein and energy than those on hypercaloric and protein enriched despite receiving higher volumes of EN (p < 0.05). No differences were observed in jejunal feeding with oligomeric vs. polymeric FSMP in terms of energy, protein, and volume. Continuous gastric feeding provided more protein, energy, and volume vs. bolus feeding (p < 0.05). Significant number of patients received less than 100% RDA of vitamin D (50.5%), vitamin B3 (49%), vitamin K (21.8%), vitamin B5 (64.3%), vitamin B9 (60%). Majority of the patients received less than 100% RDA of sodium (80.2%), potassium (99%), chloride (98%), calcium (67%), magnesium (87%), fluoride (99%), and iodine (43%). Approximately, 43.63% of cancer and 49.9% of neurological patients received less than 1 g/kg/day of protein and 51.7% of cancer and 55.5% of neurological patients received less than 25 kcal/kg/day. Conclusion Awareness of the available compositions of FSMP and advantageous profiles of specific diets may lead to the implementation of recommendations for EN. HEN professionals need to analyze all the patient’s needs and requirements to provide more tailored matching of nutritional support.